Design and synthesis of peptide-based chimeric molecules to induce degradation of the estrogen and androgen receptors - Yokoo, Hidetomo; Ohoka, Nobumichi; Naito, Mikihiko; Demizu, Yosuke (Bioorganic & medicinal chemistry, 2020)
[Display omitted] Peptide-based inducers of estrogen receptor (ER) α and androgen receptor (AR) degradations via the ubiquitin–proteasome system (UPS) were developed. The designated inducers were composed of two biologically active scaffolds: the helical peptide PERM3, which is an LXXLL-like mimic of the coactivator SRC-1, and various small molecules (MV1, LCL161, VH032, and POM) that bind to E3 ligases (IAPs, VHL, and cereblon, respectively), to induce ubiquitylation of nuclear receptors that bind to SRC-1. All of the synthesized chimeric E3 ligand-containing molecules induced the UPS-mediated degradation of ERα and AR. The PERM3 peptide was applicable for the development of the ERα and AR degraders using these E3 ligands.